Skewed Lung CCR4 to CCR6 CD4+ T Cell Ratio in Idiopathic Pulmonary Fibrosis Is Associated with Pulmonary Function - Adegunsoye, Ayodeji; Hrusch, Cara L.; Bonham, Catherine A.; Jaffery, Mohammad R.; Blaine, Kelly M.; Sullivan, Meghan; Churpek, Matthew M.; Strek, Mary E.; Noth, Imre; Sperling, Anne I. (Frontiers in Immunology, 2016)
Rationale: Idiopathic pulmonary fibrosis (IPF) is a progressive, fatal lung disease. While it has been suggested that T cells may contribute to IPF pathogenesis, these studies have focused primarily on T cells outside of the pulmonary interstitium. Thus, the role of T cells in the diseased lung tissue remains unclear. Objective: To identify whether specific CD4 T cell subsets are differentially represented in lung tissue from patients with IPF. Methods: CD4 T cells subsets were measured in lung tissue obtained from patients with IPF at the time of lung transplantation, and from age- and gender-matched organ donors with no known lung disease. Subsets were identified by their surface expression of CCR4, CCR6, and CXCR3 chemokine receptors. CD4 T cell subsets were correlated with measurements of lung function obtained prior to transplantation. Results: Compared to controls, IPF patients had a higher proportion of lung CD4 T cells, a higher proportion of CCR4 CD4 T cells, and a lower proportion of CCR6 CD4 T cells. The increase in CCR4 CD4 T cells in IPF lung tissue was not due to increased Tregs. Intriguingly, the increase in the ratio of CCR4 cells to CCR6 cells correlated significantly with better lung function. Conclusions: Our findings suggest a new paradigm that not all T cell infiltrates in IPF lungs are detrimental, but instead, specialized subsets may actually be protective. Thus, augmentation of the chemokines that recruit protective T cells, while blocking chemokines that recruit detrimental T cells, may constitute a novel approach to IPF therapy.